2015
DOI: 10.3141/2486-09
|View full text |Cite
|
Sign up to set email alerts
|

Use of Access Travel Time to Estimate the Impact of Driveway Restrictions on Corner Lot Developments

Abstract: The types of data needed to assess the economic impacts of access management treatments on businesses, such as net profits or tax revenue, are difficult to obtain in a consistent and reliable manner. As a result, most research efforts on the topic have used subjective data collected through surveys and interviews, as well as less direct data variables, such as long-term land values. Although these efforts are valuable and insightful, their findings are difficult to apply to small-scale access decisions about a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The economics-based literature indicates that access management projects, including median installations and driveway restrictions, have little to no negative impact on the property value or vitality of adjacent businesses ( 11 , 12 ). Additionally, a previous study of driveway restriction impacts on corner lot developments suggests that when a minor roadway access is present, providing unrestricted access to the major roadway does not reduce the amount of travel time required to enter and exit the development, particularly at higher roadway volumes ( 13 ). However, it is reasonable to assume that restricting the sole access point to a development will have a tangible impact on the travel patterns of development owners and patrons, even if that impact does not result in decreased business vitality.…”
Section: Development Of the Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The economics-based literature indicates that access management projects, including median installations and driveway restrictions, have little to no negative impact on the property value or vitality of adjacent businesses ( 11 , 12 ). Additionally, a previous study of driveway restriction impacts on corner lot developments suggests that when a minor roadway access is present, providing unrestricted access to the major roadway does not reduce the amount of travel time required to enter and exit the development, particularly at higher roadway volumes ( 13 ). However, it is reasonable to assume that restricting the sole access point to a development will have a tangible impact on the travel patterns of development owners and patrons, even if that impact does not result in decreased business vitality.…”
Section: Development Of the Methodologymentioning
confidence: 99%
“…As shown in Table 2, a more extensive secondary network is associated with a higher rating because driveway restrictions and congestion levels will have a lesser impact on patrons needing to access adjacent developments because of the presence of alternative routes. Previous research has suggested that, depending on volume levels, unrestricted access is not necessarily beneficial to adjacent businesses even though business owners may claim otherwise ( 13 ). The authors selected the ratings in Table 2 to represent the trends more commonly associated with good access management practices (e.g., divided roadways are preferable to undivided roadways).…”
Section: Development Of the Methodologymentioning
confidence: 99%